Russian Anti-Scientology Technology and the Ukrainian War - Šorytė, Rosita (The journal of CESNUR, 2023)
From the early 1990s in Russia the study of “cults” with the aim of eradicating them has been presented as a “science” inspiring a specific legal and administrative technology. Using the Church of Scientology as a case study, the paper claims that this combination of (pseudo-) science and technology in Russia went through three different phases: “sectology” and “spiritual security” in the 1990s; “extremism studies” and anti-extremism laws in the 2000s; and “destructology” and statutes against “undesirable organizations” in the 2010s, with harsher measures introduced after the war of aggression against Ukraine started in 2022. Scientology was declared an “undesirable organization” in 2021, which offers to the Russian state new tools of repression after the law on such groups was amended in 2022.